Improvements to the Operational Administration System at PT Widya Herbal Indonesia - Maheswari, Evany Nur Fitri (Journal Research of Social Science, Economics, and Management, 2026)
Operational administration is a crucial function in supporting the smooth management of documents and work processes, thus directly impacting work efficiency. This study aims to analyze the causes of the suboptimal operational administration system at PT Widya Herbal Indonesia. This research was conducted as part of an internship at PT Widya Herbal Indonesia, where the author was involved in operational administration activities such as document management, data recording, and archiving of company documents. The study employed a qualitative descriptive approach using secondary data obtained from the company from February to April 2025, which was analyzed descriptively using SPSS. Furthermore, a fishbone diagram (cause and effect) was used as an analytical tool to systematically identify the root causes of the problems. The results indicate that the operational administration condition has not changed or improved significantly during the observation period. These main problems are caused by limited administrative staff, inconsistent implementation of SOPs, and suboptimal utilization of the ERP system. Therefore, it is necessary to organize the work system, improve understanding of SOPs, and optimize the use of ERP to improve the effectiveness and efficiency of the company’s operational administration.